Regional Autonomy and Special Autonomy: A Review of Integration in Regional Governance from the Perspective of Civic Education - Sunarso, Sunarso; Dewi Puspitasari , Chandra; Hidayah, Yayuk; Firmansyah, Akmal (Fakultas Hukum Universitas Jambi, 2024)
This study addresses the challenges and impacts of Regional and Special Autonomy in local governance, with a particular focus on the role of civic education. The central problem is understanding how these autonomy concepts influence local development and citizen participation.The objectives of this research are to analyze how Regional and Special Autonomy affect societal dynamics and local development, and to assess the role of civic education in enhancing the implementation of these concepts. A literature study approach was employed to gain a comprehensive understanding of the issue. The analysis involved reviewing a diverse range of sources, including legal documents, academic journals, and research reports. The study utilized a variety of literature sources relevant to Regional and Special Autonomy and civic education, providing a broad and deep examination of the subject matter.The findings highlight that a thorough understanding of Regional and Special Autonomy is crucial within civic education frameworks. Effective implementation of these autonomy concepts at the local level can foster greater citizen participation in development and decision-making. Additionally, civic education plays a critical role in preparing citizens to understand and engage with their rights and responsibilities, thereby supporting more inclusive and sustainable governance. The study concludes that integrating Regional and Special Autonomy with civic education is essential for enhancing local governance. A better grasp of these concepts, supported by robust civic education, can lead to more democratic, inclusive, and sustainable community development.